The toxicity of lead to the freshwater microalgae Scenedesmus and the water flea Daphnia carinata - Dang Khoa, Dinh Hoang; Hang, Pham Thi Thu; Thi Hoanh, Pham; Phi Nga, Le (Vietnam Journal of Biotechnology, 2021)
Sai Gon river is the important source for water supply in Ho Chi Minh City. However, its water quality is degrading gradually due to rapid population growth, increasing of urbanization and industrialization. The river is continuously loaded with xenobiotics released by anthropogenic activities. Among pollutants, heavy metals are considered as the most toxic elements to aquatic living organisms and human health. The aim of this study is to assess the sensibility of freshwater microalgae Scenedesmus and water flea Daphnia carinata, two fresh water species from Viet Nam to lead (Pb). After physical and chemical characterization, field water samples from the upstream of Sai Gon River was used as dilution water in toxicity tests. With water flea D. carinata, the EC50 value of 48h immobilization experiment was 121.64 µg/L for Pb. Growth inhibition of the algae cells was determined following exposure for 96 h, and EC50 values of Pb was 14,767.9 µg/L. The results showed that Pb was highly toxic to D. carinata, and harmful to freshwater algae Scenedesmus. Based on the observed high sensitivity with Pb, D. carinata is a potential bioindicator for the assessment of Pb pollution in Sai Gon river. While lead-tolerance algae Scenedesmus calls for further investigation on metal uptake capacity and utilization in Pb contaminated water treatment